Formação dos vórtices ciclônicos de médios níveis - Silva, Thaise Gomes da (2017)
Short-term weather forecasting is based on the analyses of the atmospheric systems and so the main aim of the study was determination and analyses of the processes of the Middle Tropospheric Cyclonic Vortex (MTCV) formation. Data of the European Center for Medium-Range Weather Forecasts were used for the meteorological fields elaboration, using for MTCVs identification, determination of the formation processes and evaluation of the structure and vertical movements. Satellite images Goes12+Meteosat9 from the Center for Weather Forecasting and Climate Studies were used to verify cloudiness in the vortex region. Rainfall data of the Secretariat of the Alagoas State for the Environment and Water Resources were used to evaluate the influence of the MTCV in the Alagoas weather. Sixty two cases of the vortex occurrence during 2010 were identified and analyzed in the study. There were detected 19 cases lasting 12-24 hours and 15 cases of MTCV lasting 30-42 hours. MTCV can be formed at the level 700 hPa in around 55% (34 cases) of all vortexes. The most frequent layer of performance was between 700-600 hPa in 29% (18 cases) of cases and 19% (12 cases) of MTCVs were located only at the level 700 hPa during their lifetime. The MTCVs were formed in the trough on the Eastern Stream (Type I), Western Stream (Type II) and formed in the currents of the two hemispheres and in southern current (Type III). Ten subtypes were determined within these three types of the VCMN formation processes. Two more frequent subtypes were determined: first subtype (Trough on the East Current with the northwest to southeast axis) of Type I presented 17 cases and the second subtype (Trough on the Western Stream with southeast to northwest axis) of Type II presented 13 cases. The values of more frequent vorticity were -3x10-5 and -4x10-5 s-1. Weak values of divergence and convergence were detected in all cases, but 16 cases presented only convergence. It was observed that 32 cases presented sinking before the formation of the vortex center and 35 cases presented sinking and lifting during the formation of the vortex center. Low level clouds and a maximum precipitation of 11 mm/24 h in the Atalaia municipality were observed in the study case. It was able to emphasize the relevance of these results for short-term weather forecasting and the necessity of more studies of MTCVs.